Towards in-situ TEM for Li-ion Battery Research. (October 2018) - Wheatcroft, Laura; Özkaya, Doğan; Cookson, James; Inkson, Beverley J
Abstract: Due to recent developments in new battery materials for higher energy density applications there has been growing interest in new characterization techniques capable of time-resolved in situ/in operando analysis of dynamic Battery systems. This review provides an overview on recent development of liquid cell transmission electron microscopy (TEM) for Li-ion battery research and discusses the challenges, highlighting potential research areas. In-situ TEM offers the opportunity to study phenomena including solid electrolyte interphase (SEI) formation and phase changes during battery operation. There are two main challenging areas for in-situ TEM research (1) designing an in-situ TEM electrochemical cell that mimics a 'real' cell and (2) quantifying beam damage caused by electron irradiation of the electrolyte.